Does the feeding frequency influence the growth performance of European perch juveniles (Perca fluviatilis) during intensive rearing? - Molnár, Áron; Dajka, Bence; Fehér, Milán (Acta Agraria Debreceniensis, 2022)
The European perch (Perca fluviatilis) is a predatory fish species. Its aquaculture production is increasing worldwide. Feeding and the frequency of feeding are important elements of intensive fish rearing. The aim of our experiment was to examine the optimal distribution of the amount of feed, at the same feed rations. The experiment lasted 42 days. Three treatments were applied in 4–4 replications. The first treatment was feeding twice per day (T2), the second treatment was feeding three times a day (T3), and the third group was fed four times a day (T4). 10 European perch juveniles were stocked per tank, with an individual mean body weight of 3.93 ± 0.06 g at the start of the experiment. The survival rate (S%) was above 90% for all treatments. The T2 treatments produced the most favourable harvest weight (13.96 ± 0.14 g) and specific growth rate (SGR = 3.08 ± 0.01% day-1), but no significant differences were observed between groups. In terms of feed conversion ratio, the best result was obtained by (T3) (FCR =1.06 ± 0.18 g g-1), but no significant difference was found for this indicator neither. The results of the trial indicate that the feeding frequency does not influence the production parameters.